Surface-sensitive NMR detection of the solid electrolyte interphase layer on reduced graphene oxide - Leskes, Michal; Kim, Gunwoo; Liu, Tao; Michan, Alison L.; Aussenac, Fabien; Dorffer, Patrick; Paul, Subhradip; Grey, Clare P. (American Chemical Society, 2017)
Forming a stable solid electrolyte interphase (SEI) is critical for rechargeable batteries’ performance and lifetime. Understanding its formation requires analytical techniques that provide molecular-level insight. Here, dynamic nuclear polarization (DNP) is utilized for the first time to enhance the sensitivity of solid-state NMR (ssNMR) spectroscopy to the SEI. The approach is demonstrated on reduced graphene oxide (rGO) cycled in Li-ion cells in natural abundance and 13C-enriched electrolyte solvents. Our results indicate that DNP enhances the signal of outer SEI layers, enabling detection of natural abundance 13C spectra from this component of the SEI on reasonable time frames. Furthermore, 13C-enriched electrolyte measurements at 100 K provide ample sensitivity without DNP due to the vast amount of SEI filling the rGO pores, thereby allowing differentiation of the inner and outer SEI layer composition. Developing this approach further will benefit the study of many electrode materials, equipping ssNMR with the necessary sensitivity to probe the SEI efficiently.